Ekoefektywność w kontekście zarządzania strategicznego - Ziółkowski, Bożydar (Eco-effectiveness in the Context of Strategic Management, 2008)
Among many new concepts of management eco-effectiveness is as a strategy a matter of a great interest. The aim of this paper is presenting eco-effectiveness theory as well as practical experiences in the context of strategic use. The conducted discussion is based on the examples of successful products from selected enterprises which aimed to improve their own effectiveness by strategy consistent with the principle of cradle to cradle.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 490-497